One-Pot Synthesis of 2,5-Dihydrosiloles and Their Silole-Annulated Analogs Starting from Alkynylsilanes with a Terminal Alkynyl Group - Tok, Oleg L; Bould, Jonathan; Dušek, Michal; Cvačka, Josef (The Journal of organic chemistry, 2021)
In contrast to the reaction of vinyl(alkynyl)silanes with 9-BBN-H, leading to the quantitative formation of 5-R-4-(9-BBN)-2,3-dihydro-1H-siloles, treatment of bis(alkynyl)silanes bearing one terminal alkynyl group with 2 equiv of 9-BBN-H followed by methanolysis afforded 5-R-4-(9-BBN)-2,5-dihydro-1H-siloles with yields of 85-90% (by NMR integration). The reaction proceeds via a double 1,2-hydroboration of the terminal triple bond with the formation of the geminal diborane followed by ring closure via intramolecular 1,1-carboboration of the remaining alkynyl fragment. Depending on the nature of the substituent R in position 5, the allylic BBN group locates in position 3 (R = Ph) or position 5 (R = SiHMe2, SiMe3) to give 2,3- or 2,5-dihydrosiloles, respectively. The protodeborylation of the allylic BBN group with MeOH of both 3,4-(9-BBN)2-2,3-dihydro- and 4,5-(9-BBN)2-2,5-dihydrosiloles results in the exclusive formation of 4-(9-BBN)-2,5-dihydrosiloles. In all cases, the formation of 10-12% of 2-R-2,4-(9-BBN)2-2,3-dihydrosilole minor isomers has been observed, which occurs from vicinal diboranes formed as side products by a second hydroboration of the terminal triple bond. Similarly, treatment of the tri- and tetraalkynes containing a terminal triple bond with 2 equiv of 9-BBN-H followed by treatment with methanol resulted in the high-yield formation of 1,2,6,6a-tetrahydro-1,6-disilapentalenes and 2,6,7,7a-tetrahydro-1,6,7-trisila-1H-cyclopenta[a]pentalenes, respectively.